Observations on the Radium Treatment of Vesical Carcinoma - Morson, A. Clifford (1928)
A review of the position of radium-therapy in 1913 and of the knowledge of this subject acquired by the year 1914.—The discoveries of the relationship of the fibroblast to the control of cancer.—In elaborating the technique for vesical carcinoma, a comparison of the methods of approaching the tumour must be carefully studied, sepsis controlled and the difficulty of determining the sensitiveness of the individual's cell realized.—Possible damage to the ureter and the iliac vessels and other complications of radium applications must also be considered.—It is possible that chemical substances which give off secondary radiations may prove of great assistance in association with radium treatment.—A record is given of twelve cases which have been treated since 1925.